The Relationship Between Parental Phubbing and Interpersonal Aggression in Adolescents: The Role of Rejection Sensitivity and School Climate. Issue 11 (June 2023) - Zhao, Jinzhe; Guo, Zhen; Shi, Huiyue; Yu, Mengke; Jiao, Liying; Xu, Yan
The impact of parental phubbing has attracted the attention of researchers, especially concerning adolescents' online behavior. However, limited research has studied the influence of parental phubbing on interpersonal aggression, including the underlying mechanism. Grounded in parental acceptance–rejection theory, the present study investigated the association between parental phubbing and interpersonal aggression as well as the mediating role of rejection sensitivity among adolescents. Additionally, school climate was explored as a moderator based on social ecological theory. The multiple questionnaires were completed by 914 Chinese adolescents ( M = 12.61; SD = 1.73; 49.78% girls). The results revealed a positive correlation between parental phubbing and aggression, which was mediated by rejection sensitivity. That is, adolescents who experienced parental phubbing were more likely to exhibit rejection sensitivity, which further triggered aggression. Moreover, school climate acted as a moderator in the model. Specifically, we found no significant moderating effect of school climate on parental phubbing and aggression. However, school climate moderated the relationship between rejection sensitivity and aggression. A positive school climate buffered the associations of rejection sensitivity and aggression. Additionally, school climate moderated the relationship between parental phubbing and rejection sensitivity. The relationship between parental phubbing and rejection sensitivity became nonsignificant when adolescents were in a negative school climate, and those adolescents reported higher rejection sensitivity whether they experienced parental phubbing or not. Parental phubbing was more strongly associated with adolescents' rejection sensitivity in a positive school climate. With a lower level of parental phubbing, rejection sensitivity is sharply reduced. The results deepen our understanding of the relationship between parental phubbing and aggression and its underlying mechanisms. It also implicates preventative interventions to reduce the risk of parental phubbing in interpersonal aggression among adolescents.